Central Sleep Apnoea and Arrhythmogenesis After Myocardial Infarction—The CESAAR Study - Reshetnik, Alexander; Puppe, Swetlana; Bonnemeier, Hendrik (Frontiers in Cardiovascular Medicine, 2019)
The prevalence of sleep disordered breathing (SDB) after acute myocardial infarction (AMI) is high. However, little is known about predominant SDB type and the impact of SDB severity on arrhythmogenesis. We conducted a prospective single-center observational study and performed an unattended sleep study and Holter monitoring within ten days after AMI and an unattended sleep study 11.3 months after AMI. All patients were included from department of cardiology at University Hospital Schleswig-Holstein, Lübeck, Germany. A total of 202 subjects with AMI (73.8% with ST-elevation; 59.8 years;73.8% male) were included. The mean BMI was 27.8 kg/m2 and the mean neck/waist circumference was 41.7/103.3 cm. The mean left ventricular ejection fraction was 56.6%. The SDB prevalence defined as apnoea-hypopnea-index (AHI) ≥ 5/h was 66.7% with 44.9% having central (CSA) and 21.8% obstructive sleep apnoea (OSA). The mean AHI was 13.8 1/h. In 10.2% nsVT was detected in the Holter monitoring. AI>23/h was independently associated with higher risk of nsVT in the subacute AMI period. SDB is highly prevalent and CSA a predominant type of SDB in the subacute phase after uncomplicated AMI treated with modern revascularization procedures and evidence-based pharmacological therapy. Severe SDB is independently associated with higher risk for nsVT in the subacute AMI period and its course should be monitored as it can potentially have negative impact on relevant outcomes of AMI patients. Further prospective studies are needed to assess long-term follow up of SDB after AMI and its impact on mortality and morbidity.